Effect of orthopedic surgery delay and counseling on postoperative complications and mortality rate in patients aged over 55 years in a teaching hospital - Ladan Ghadami; Seyed Amir Mahlisha Kazemi Shishvan; Arash Shirdel; Abolfazl Dorost; Abbas Homauni; Nayereh Sadat Rohollahi; Arash Jafarieh (Wolters Kluwer Medknow Publications, 2019)
AIM: The purpose of this study was to investigate the effects of delay in the operation and counseling on postoperative complications and mortality rates in elderly patients. METHODOLOGY: The present study was a descriptive cross-sectional research. Population of this study was the entire elderly hospitalized patients who aged over 55 years for emergency orthopedic surgeries in a teaching hospital in Tehran. Surgery delays were then determined after examining the checklists, and the relationship between the variables and surgery delays, number of preoperative counseling, complications, and mortality rate was evaluated. Data were analyzed using the Mann-Whitney U-test and Pearson correlation coefficient in SPSS 18 at a 0.05 significance level. RESULTS: Overall, 89.9% of the patients had counseling. The average hospitalization days were 5 days until surgery, and the standard deviation was 0.50. The mean counseling number was 5.5. The relationship between number of counseling and surgical delays was significant. Delay in surgery in this age group, mortality, and the chances of death have become 2.7 times more than who had not a surgical delay. No significant relationship was observed between surgery delay and the incidence of Deep Venous Thrombosis (P = 0.102), postoperative sepsis and Myocardial Infarction (P = 0.337), embolism (P = 0.505), and postoperative Cerebrovascular Accident (P = 0.153). CONCLUSIONS: The delay in surgery in the elderly causes an increase in mortality. Considering the findings of this study and the importance of emergency orthopedic surgeries in the elderly, to reduce the surgical delays and the mortality rate in the elderly, the establishment of a surgical team for elderly patients in hospitals is recommended.